Is sporadic Alzheimer disease the brain type of non-insulin dependent diabetes mellitus?: a challenging hypothesis - Hoyer, Siegfried (Journal of neural transmission, 1998)
The hypothesis is forwarded that sporadic late-onset Alzheimer disease is caused by non-insulin dependent diabetes mellitus which is confined to the brain. This hypothesis is based on the findings of Frölich and coworkers (this volume) who clearly demonstrate a perturbation of the neuronal insulin/insulin receptor signal transduction pathway which is considered to be the pathobiochemical basis for the drastic reduction in glucose/energy metabolism in Alzheimer brain. As a consequence of this abnormality, advanced glycation end products are formed. Münch et al. (this volume) evaluate the impacts of the latter related to oxidative stress and the formation of β-amyloid and neurofibrillary tangles.